Selection strategies considering varietal differences with respect to egg characters of mulberry silkworm, Bombyx mori L. - Ahsan, M Kamrul (University Journal of Zoology, Rajshahi University, 2013)
The genotypic variability and correlation coefficients were studied in 27 indigenous multivoltine varieties of mulberry silkworm, B. mori L. for six egg characters. The genotype was highly significant for all the characters under studied. Least difference between genotypic and phenotypic coefficient of variation were observed. Majority of the characters showed high heritability comparing with dead egg percentage. Furthermore Unfertilized egg percentage showed high genetic advance together with high heritability but HP and EW showed high heritability and low genetic advance. These indicate the importance of additive and non-additive gene effect of these characters respectively. Total number of egg laid by female, hatching percentage, and blue egg percentage showed both positive and negative significant correlation to each other at both the phenotypic and genotypic levels. The results suggest that these characters specially total number of egg laid by female, blue egg percentage and unfertilized egg percentage appeared as importance in selection programme for genetic gain in B. mori. DOI: http://dx.doi.org/10.3329/ujzru.v31i0.15375 Univ. j. zool. Rajshahi Univ. Vol. 31, 2012 pp. 19-22